Respostas

2014-06-05T23:58:23-03:00
2(x+5)-3(5-x)=10                                                                                                                                                                                                                                                                                                                                                                       2x+10-15+3x=10                                                                                                             2x+3x=10-10+15                                                                                                             5x=15                                                                                                                            
      5                                                                                                                                                                                                                                                                                                                                                                                                            x=3
2014-06-05T23:59:19-03:00
2(x+5)- 3 (5-x) =10
2x +10 -15 +3x =10
5x=10-10+15
5x=15
x=15/5
x=3

3(x-2)= 4(3-x)
3x -6 = 12-4x
3x+4x=12+6
7x=18
x=18/7

4x-1=3(x-1)
4x-1= 3x-3
4x-3x=-3+1
x=-2